Functional polymeric materials for hard water treatment a comprehensive review - Olivia Hernández-Cruz; Gerardo Enrique Córdova-Pérez; Jorge Raúl Cerna Cortez (Discover Materials)
Abstract Hard water, characterized by elevated concentrations of calcium (Ca²⁺) and magnesium (Mg²⁺) ions, poses substantial challenges to domestic, industrial, and environmental systems. Conventional treatment methods—such as chemical precipitation, ion exchange, and membrane separation—are often limited by high operational costs, fouling, and poor selectivity. Recent studies have demonstrated that polymer-based materials offer promising alternatives due to their tunable physicochemical properties, cost-effectiveness, and potential for environmental compatibility. For example, functionalized polyamides and polysulfone membranes have achieved over 95% removal efficiency for Ca²⁺ and Mg²⁺ ions, while hydrogels and bio-based polymers show high regeneration capacity and reduced fouling. Radiation-induced grafting, interfacial polymerization, and nanofiller incorporation have further advanced membrane performance by improving charge density, permeability, and ion selectivity. This review critically evaluates current strategies employing polymeric materials for hard water treatment, identifies major limitations in scalability and long-term durability, and outlines future research directions for developing sustainable, high-performance polymer systems. The insights aim to guide the rational design of next-generation materials capable of addressing global water quality challenges.